Video versus live lecture courses: a comparative evaluation of lecture types and results. Issue 1 (1st January 2018) - Brockfeld, Thomas; Müller, Bringfried; de Laffolie, Jan
ABSTRACT: Background : Video lectures are an increasingly popular format. They allow an individual choice of time, place and speed of learning. Objective : The aim of the present study was to compare whether video lectures are as effective as live lectures to impart the complete contents of the clinical part of the medical exam. The study also examines whether students prefer live or video lectures and for what reason. Design : In 2014, a preparatory course was held at the University of Göttingen to train medical students for the clinical part of the medical exams. Three-quarters of the participants received 41 four-hour lessons live, while the same lessons were shown on video to the remaining quarter. The assignment to the video group changed daily, so that all students saw both live and video lectures. To compare the effectiveness, it was evaluated for 205 students how video and live students answered the 301 multiple choice questions of the medical exam. Results : There is hardly any difference regarding effectiveness. 36, 735 of 46, 926 questions (78.283%) were correctly answered by the live group, while 11, 617 of 14, 779 questions (78.605%) were correctly answered by the video group (n.s., p = 0.407, effect size ω = 0.003337). There were some differences in subjective evaluation: 48% of students preferred live lessons, 27% preferred video lessons and 25% stated 'neutral'. The items 'learning atmosphere', 'ability to concentrate', 'presence of other students' and 'acoustic intelligibility' were assessed significantly better for the video courses than for the live courses. No item of the live course was rated better than in the video course. Conclusions : Video and live lectures are equally effective in preparation for the clinical part of the medical exams. Video lectures offer many benefits for the students and for the faculties, and may complement and partly replace conventional live events.